ANALISIS PENGARUH CR, TATO, ROA TERHADAP RETURN SAHAM: STUDI KASUS PT. BANK MANDIRI - Putri Hana Febrian; Amanda Diva Mia Putri; Putra Fajar Maulana; Renny Oktafia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Stock price fluctuations are closely related to stock returns because changes in stock prices can generate profits or losses for investors and ultimately affect investment returns. Based on previous research, the reality of the impact of financial performance ratios on stock returns makes investors really need an understanding of the actual performance of the bank to make better investment decisions. The financial performance ratios used in this study are Current Ratio (CR), Total Assets Turnover (TATO), and Return on Assets (ROA). Therefore, this study aims to develop hypotheses about the influence of variables that will be used in future research, especially in the context of the case study of PT Bank Mandiri. Data was collected through a literature review of related articles to see previous research that became a reference in writing this article. The results showed that Current Ratio, Total Assets Turnover and Return on Assets have a positive effect and have a relationship to stock returns both individually and together. Overall, the company's success in managing these financial ratios will have a positive impact on the company's stock performance.